Correlates of Acceptance of Wealth Inequality: A Moderated Mediation Model - Cheng, Grand H.-L.; Chan, Darius K.-S.; Yeung, Dannii Y. (Frontiers in Psychology, 2019)
Wealth inequality is a prevalent social issue. The present study focuses on acceptance of wealth inequality, and considers personal income, perceived upward mobility, and future time perspective as its antecedents, and collective action intention as its outcome. With reference to the social identity literature and socioemotional selectivity theory, we posit a conditional indirect effect of income on collective action intention through acceptance of wealth inequality: only when mobility and future time perspective are relatively high, higher income is associated with higher acceptance of wealth inequality and in turn, lower collective action intention. Moderated mediation findings, based on territory-wide phone survey data from 866 Hong Kong adults, supported this prediction. This work indicates the relevance of an individual-level instrumental perspective to the understanding of acceptance of wealth inequality as well as collective action intention.